Novel educational training of para medical professionals in cervical cancer screening - Sneha Raj; Abhay K. Kattepur; T.S. Shylasree; Gauravi A Mishra; Akshay Patil; Sharmila Pimple; Santosh Noronha; C.S. Pramesh (Elsevier, 2023)
Background: Cervical cancer is a public health problem in India due to weak national screening policy compounded by lack of resources including scarcity of trained personnel to carry out community-based screening program. Para medical professionals (PMPs) are closely related to women in local communities. Hence, training PMPs by incorporating novel technology and reduced time duration to achieve adequate competence in screening is an area underutilized and needs to be explored. Materials and methods: A pilot cross sectional analytical study was conducted at a tertiary referral cancer center using a shorter version of educational intervention of 2 weeks duration (EI2W) involving PMPs. Pre- and post-training assessment of knowledge, attitude, and practice (KAP) was done using questionnaires consisting of 5 domains viz. awareness of cervical cancer, awareness of cervical pre-cancer, practical screening methodology (practice oriented), data management and aspects of human papilloma virus (HPV). Wilcoxon signed-rank test was used for comparison and the degree of change was measured using analysis of covariance (ANCOVA). A p value of <0.05 was considered significant. Results: 118 PMPs were included. There was a significant improvement in scores of all domains (except cervical pre-cancer domain), following introduction of EI2W. Knowledge scores, post EI2W was better in Auxiliary Nurse Midwives (ANMs) than other participants. Awareness regarding cervical cancer was higher with more years of experience. The KAP analysis showed excellent interrater reliability in the practice 0.726 (0.649-0.792) followed by knowledge domain 0.711 (0.626-0.783). Conclusion: EI2W was effective in significantly improving the competence of PMPs, thus reducing human resource constraints in cervical cancer prevention and elimination.